Korean Translation of the GRADE Series Published in the BMJ, ‘GRADE: Incorporating Considerations of Resources Use into Grading Recommendations’ (A Secondary Publication) - Hong Wook Kim; Jae Hung Jung; Do Kyung Kim; Ho Won Kang; Ja Yoon Ku; Hyun Jin Jung; Eu Chang Hwang (Urogenital Tract Infection)
This article is the fifth translation of a GRADE series published in the BMJ for incorporating the considerations of resources use into grading recommendations. Clinical recommendations inevitably involve judgments about the allocation of resources use (costs). Although costs differ from typical healthcare outcomes, such as mortality, morbidity, and quality of life, costs are another potentially important outcome that differs across and within a jurisdiction. A balance sheet is a useful method for determining if the net benefits are worth the incremental costs. Resource use, not just monetary values, should always be presented in an evidence profile. Formal economic modeling may or may not help judge the certainty of the evidence for resource use.